'Backroom Boys': Occupational Dynamics in Crime Scene Examination. (August 2014) - Wilson-Kovacs, Dana
Despite a sustained preoccupation with crime scene investigation in policing and instructional literatures, government reviews and media accounts, the crime scene examiner has received scant sociological attention. Focusing on scientific support personnel in an English police force, this article analyses how embedded actors who routinely facilitate the provision of crime scene examination reflect on their role and position in the investigative process. The analysis draws on data collected in a small number of semi-structured interviews with stakeholders at different levels of seniority, in order to map an understanding of the inter and intra-professional interactions, exchanges, dependencies and negotiations employed by those working at the coalface of investigative practice. Hoping to illuminate some of the sense-making practices behind the enactment of forensic activities, the discussion examines the articulation of professional identities and the conclusion reflects more broadly on the processes of professionalisation and discourses of professionalism that accompany standardised forensic accomplishments.